Percepción social de las actitudes cognitivas de Aloe vera L. "sábila", Iquitos - Loreto, 2022 - Soto Chong, Moises Alejandro (2023)
This descriptive level research work was carried out in the city of Iquitos, the main objective being to determine how cognitive social perception affects the sale and use of aloe vera. The survey was aimed at vendors of aloe vera-based beverages and consumers. All vendors in forklifts and 30 consumers were interviewed, the responses were recorded on a Likert scale structured sheet, with a Cronbach's alpha coefficient of 0.63, meaning good reliability. The results show the cognitive social perception of a low, medium to high level, thus, more than half at a medium to high level say they know it and that they cultivate it in orchards, gardens, that the majority (70%) like the products made with the gel, know its medicinal properties, consuming it as a distraction or relaxation, very few (10%) at a very good level say they know its healing properties, most say they buy aloe-based beauty products, being used ancestrally as medicinal and that cures a specific disease, consuming it more frequently and preferably. The social perception of the sale of aloe vera stalks in ambulatory carts, the majority say is attractive and that they regularly consider that the rulers promote this activity and that the vast majority (80.0%) with sales of stalks of size, width, thickness and appropriate weight for consumption and harvested from the basal part of the plant, which are mature leaves after the emission of the first floral axis of the plant; however, (the majority sell whole plant and immature stalks), in Iquitos there is little production, medium quality, very soft and watery consistency. Commercial indicators report in averages by sellers, that the majority of 8 to 12 years old, sell 11.8 leaves per day, purchase 7.0 soles per 572.0 g leaf, coming from Huánuco, Tarapoto and Iquitos, from other regions they are of better quality, higher length, width, thickness, weight and consistency of the gel.